Pengaruh Stres Kerja Dan Lingkungan Kerja Terhadap Kinerja Pegawai Pada Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Aceh Tengah - Khairani, Elisa; Sabri, Sabri; Fitra, Yasri (Jurnal Ilmiah Ilmu Manajemen, 2024)
This research is based on the problem of whether work stress and the work environment influence employee performance at the Population and Civil Registration Service and the aim of the research is to determine the effect of work stress and the work environment on employee performance at the Population and Civil Registration Service. The research location at the Population and Civil Registration Service, Jl Sentosa, had 47 respondents, which was applied by census, then the data was collected using a questionnaire and analyzed quantitatively with multiple linear regression equipment, namely Y = a + b1X1 + b2X2 with the help of the SPSS version of the program 25. The research results show Y = 1.552 + 0.396X1 + 0.297X2 so that partially work stress has an effect on the performance of employees at the Population and Civil Registration Service. That is, it is proven that the tcount > ttable value is 2.937 and the ttable value is 2.017. Partially, the work environment influences employee performance at the Population and Civil Registration Service, which is proven by the tcount > ttable value of 2.242 and the ttable value of 2.017. Simultaneously, work stress and the environment influence the performance of employees at the Population and Civil Registration Service. Proven by the value of Fcount > Ftable, namely 19.709 and Ftable of 3.21. That the work stress and environmental variables influence performance is 47.3%. The rest is influenced by other variables. The relationship between work stress and environmental variables and performance is strong. 0.687 or 68.7%. With a strong category.